Coadministration of Voriconazole and Rifabutin Can Increase the Risk of Adverse Drug Reactions in Patients With Multiple Infections - Kim, Yoonjin; Bae, Sungyeun; Huh, Ki Young; Joo, Jong Sun; Lee, Jikyo; Song, Sang Hoon; Yu, Kyung-Sang; Jang, In-Jin; Oh, Jaeseong (Therapeutic drug monitoring, 2025)
Coinfection of tuberculosis or nontuberculous mycobacteria and Aspergillus presents a challenge in medication selection because of the pharmacokinetic interactions between rifampin and voriconazole. Some researchers have suggested the use of rifabutin as an alternative to rifampin because of its lower hepatic cytochrome P450 enzyme induction potency despite its contraindication to drug labels. This study presents clinical cases of voriconazole and rifabutin coadministration and their potential risks. This retrospective study was conducted using clinical data from patients who met the following criteria: (1) admitted to Seoul National University Hospital between July 2014 and August 2023 and (2) concurrently administered rifabutin and voriconazole for more than 5 days. Among the 6 patients analyzed, 4 experienced adverse drug reactions (ADRs). Three patients experienced visual and auditory hallucinations, lower extremity numbness, or delirious behavior. Two patients had prolonged the time from the start of the Q wave to the end of the T wave intervals, and 1 had elevated aspartate aminotransferase and alanine aminotransferase levels. In addition, 2 patients experienced severe nausea, poor oral intake, and weight loss. Despite receiving 1.81-fold the recommended voriconazole dosage, a therapeutic concentration (1.0-5.5 mg/L) was not achieved because of cytochrome P450 induction by rifabutin. However, during septic shock, the voriconazole concentration increased by 13.7- to 36-fold. Concurrent use of rifabutin and voriconazole was associated with ADRs, including the time from the start of the Q wave to the end of the T wave prolongation, hallucinations, and severe nausea. Moreover, initially, there was a significant decrease in voriconazole concentrations; however, these concentrations substantially increased during septic shock. Therefore, it is essential to monitor drug concentrations and ADRs during concurrent use of voriconazole and rifabutin.